The three pillars of sustainability trends: A bibliometric analysis - Hermosa Del Vasto, Paola (European Public & Social Innovation Review, 2024)
Introduction: The purpose of this article is to identify the progress made in sustainability and its three pillars, environmental, social and economic, in order to extract the core aspects and contribute to economic growth, social progress and the promotion of environmental sustainability. Methodology: A bibliometric analysis was carried out on the sample of 4.166 articles retrieved from the Scopus database using VOSviewer, a software tool commonly used in bibliometric studies and focusing on the main dimensions of sustainability: environmental, social and, economic. This paper presents the theoretical aspects of the study of journals, researchers, or individual publications, keywords, institutions based on citation, bibliographic coupling, co-citation. Results and discussions: The results suggest that sustainability measurement is an emerging area of research. Influential categories are social sciences, environmental sciences, and business, management, and accounting. Prominent authors such as Scholtens, Zaman, and Berman contribute to the field. Five distinct clusters have been identified: “sustainable development”, “sustainability”, “economics”, “economic analysis”, “decision support systems”. The top keywords in the social cluster (“economics and social effects”), the economic cluster(“economics”, “commerce”, “economic development”, “financial system”, “financial sustainability”, “environmental economics”), and the newest but strongest environmental cluster (“climate change”, “environmental protection”, “environmental management”). Conclusions: It also presents the expectations and challenges of sustainability, allowing trends to be identified and assessed. Consequently, this research will support the lines of research with more impact ton mapping in sustainability research.